2017
DOI: 10.1093/nar/gkx003
|View full text |Cite
|
Sign up to set email alerts
|

Computational approach for deriving cancer progression roadmaps from static sample data

Abstract: As with any biological process, cancer development is inherently dynamic. While major efforts continue to catalog the genomic events associated with human cancer, it remains difficult to interpret and extrapolate the accumulating data to provide insights into the dynamic aspects of the disease. Here, we present a computational strategy that enables the construction of a cancer progression model using static tumor sample data. The developed approach overcame many technical limitations of existing methods. Appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 67 publications
1
29
0
Order By: Relevance
“…Our findings support that molecular subtypes are not hardwired, and genotypes and phenotypes can shift over time [11], and show that cancer development follows common progression paths, as posited in [29]. We performed a series of interrogations that provided substantial support for the constructed model, and showed the utility of such a model for testing and generating hypotheses and providing novel insights into previous observations from the cancer-evolution perspective [28]. First, we demonstrated that the same progression pattern was repeatedly observed in additional 26 breast cancer datasets, which together with the METABRIC dataset comprise almost all of the breast tumor samples assayed over the past 15 years (> 9, 000 samples).…”
Section: Breast Cancer Progression Modelingsupporting
confidence: 80%
See 2 more Smart Citations
“…Our findings support that molecular subtypes are not hardwired, and genotypes and phenotypes can shift over time [11], and show that cancer development follows common progression paths, as posited in [29]. We performed a series of interrogations that provided substantial support for the constructed model, and showed the utility of such a model for testing and generating hypotheses and providing novel insights into previous observations from the cancer-evolution perspective [28]. First, we demonstrated that the same progression pattern was repeatedly observed in additional 26 breast cancer datasets, which together with the METABRIC dataset comprise almost all of the breast tumor samples assayed over the past 15 years (> 9, 000 samples).…”
Section: Breast Cancer Progression Modelingsupporting
confidence: 80%
“…Given the human tumor sampling limitation, we previously devised a computational strategy [28] to derive pseudo time-series data from static samples (excised tissue specimens). The design is based on the idea that each sample can provide a snapshot of the disease process, and if the number of samples is sufficiently large we can recover a visualization of disease progression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human cancer is a heterogeneous disease initiated by random somatic mutations and driven by multiple genomic alterations (Hanahan and Weinberg, 2011;Sun et al, 2017). In order to move towards personalized patient treatment regimes, cancers of specific tissues have been divided into molecular subtypes based on the gene expression profiles of primary tumors (Sørlie et al, 2001(Sørlie et al, , 2003Curtis et al, 2012;Parker et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The desire for levels of accuracy that can ultimately lead to clinical utility continues to drive the field to refine breast cancer subtypes (Shen et al, 2013;Parker et al, 2009;Sun et al, 2017;Haibe-Kains et al, 2012;Sun et al, 2014) and to identify molecular subtypes in other cancers (Abeshouse et al, 2015;Cancer Genome Atlas Network, 2014). The recent establishment of international cancer genome consortia (Cancer Genome Atlas Network, 2012;Abeshouse et al, 2015;Cancer Genome Atlas Network, 2014;Curtis et al, 2012) has generally overcome the sample size issue.…”
Section: Introductionmentioning
confidence: 99%